Nerve trunk healing and neuroma formation after nerve transection injury - Huang, Dong-Xu; Yang, Ming-Xi; Jiang, Zhen-Min; Chen, Miao; Chang, Kun; Zhan, Yong-Xin; Gong, Xu (Frontiers in Neurology, 2023)
The nerve trunk healing process of a transected peripheral nerve trunk is composed of angiogenesis, nerve fiber regeneration, and scarring. Nerve trunk healing and neuroma formation probably share identical molecular mediators and similar regulations. At the nerve transection site, angiogenesis is sufficient and necessary for nerve fiber regeneration. Angiogenesis and nerve fiber regeneration reveal a positive correlation in the early time. Scarring and nerve fiber regeneration show a negative correlation in the late phase. We hypothesize that anti-angiogenesis suppresses neuromas. Subsequently, we provide potential protocols to test our hypothesis. Finally, we recommend employing anti-angiogenic small-molecule protein kinase inhibitors to investigate nerve transection injuries.